Tipologi Inovasi Sistem Pelayanan Kependudukan Kabupaten Pasaman Barat - Deva Umarsyah; Zulkarnaini Zulkarnaini (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
Innovation in the scope of public services is one of the important elements in the government environment so that it becomes one of the solutions to public problems that are currently happening. The presence of innovation can improve the quality and satisfaction of public services to the community. The West Pasaman population service system is a public sector organization that seeks to provide services by launching various forms of service innovation in order to facilitate the community in the process of issuing population documents. This study uses the theory of Typology of Innovation by Mulgan and Albury in Khairul Muluk which aims to analyze how forms of innovation exist in the population service system of West Pasaman Regency. The method used in this study is a qualitative descriptive approach. Data collection techniques were carried out through interviews and documentation. Data analysis in the field uses the Miles and Huberman model which consists of data reduction, data presentation, and drawing conclusions. As a result, the implementation of the population system innovation of West Pasaman Regency based on the Typology of Innovation has been appropriate for every form of typology. The dominant innovation typology lies in service innovation products, which amount to fourteen innovations. Meanwhile, in the typology of service method innovation, provides convenience with direct services to the office or online-based services. The supporting factor for implementing innovation lies in the high enthusiasm of the community in managing population documents and the stability of SIAK which runs optimally.